Medical Record Classification: A Modified Genetic Algorithm for Feature Selection - Jillahi, Kamal Bakari (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Medical record classification is the process of categorizing a patient’s record as either having or not having a medical condition based on some given information (features) about the patient. Not all available features about a patient are both useful and relevant in the process of classification. As such, the need for selecting the relevant and useful features arises. Furthermore, the current growth in data dimensionality as a result of falling cost of data capture and storage also makes it necessary to feed the learning algorithm with only the required features about the patient. Over the years, the ML Community has used a number of algorithms for feature selection. One of such widely used algorithms is Genetic Algorithm (GA). Given that the performance of GA is depended on algorithm parameters and genetic operators used, this work modified the genetic operators (crossover and mutation) of the GA and used Extreme Learning Machine (ELM) which is a Single Layer Feedforward Neural Network (SLFN) with faster training time and least parameter tuning for the purpose of record classification. Furthermore, the work evaluated the performance of the proposed algorithm on 3 datasets from the UCI ML repository. The proposed algorithm showed a faster convergence, better classifier accuracy and fewer selected features than the traditional GA and other reported works. The proposed method is particularly useful in situation of time constraint, low computation power and high dimensional data.

ÖZ: Tıbbi kayıt sınıflandırma hasta hakkında bilinen tıbbi durum veya bazı verilen bilgilere (özellikler) dayalı olarak hastanın kaydını kategorize işlemidir. Sınıflandırma sürecinde hasta ile ilgili tüm bilgiler sınıflandırma için yararlı ve ilgili olmayabilir. Bu nedenle, yararlı ve ilgili bilgileri mevcut bilgiler arasından seçme ihtiyacı duymaktayız. Ayrıca, veri yakalama ve depolama maliyetini düşürme amaçlı hasta hakkında sadece gerekli özelliklere sahip olma ve bu özellikleri öğrenme algoritmalarında kullanmak için özellik seçimi önem kazanmaktadır. Yıllar geçtikçe, ML Topluluğu özellik seçimi için bir dizi algoritma kullanmıştır. Genetik Algoritma (GA) yaygın olarak kullanılan algoritmalardan biridir. GA algoritmasının performansı verilen papametreler ve genetic operatörlere bağlı olduğu gözönünde bulundurulduğundan bu çalışmada özellik seçimi için GA’nın genetic operatörleri (Çaprazlama ve Mutasyon) modifiye edilmiş ve kayıt sınıflandırma için hızlı öğrenme süresi ve az papametre kullanan Tek Katmanlı İleri Beslemeli Sinir Ağı (TKIBSA) ile Extreme Öğrenme Makinesi (EÖM) kulanılmıştır. Önerilen algoritma UCI ML deposunda bulunan 3 farklı dataset kullanılarak performansı test edildi. Önerilen algoritma geleneksel GA algoritmasından ve önerilen digger algoritmalardan daha hızlı yakınsama, daha iyi sınıflandırma doğruluğu ve daha az özellik kullanımı olduğu gösterildi. Önerilen yöntem, özellikle düşük hesaplama gücü ve yüksek boyutsal veriler durumunda yararlıdır.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2016. Supervisor: Assist. Prof. Dr. Ahmet Ünveren.
Keywords: Computer Engineering Department; Genetic algorithms; Feature Selection; Filter Methods; Wrapper Methods; Classification; Genetic Algorithms; Convergence; Extreme Learning Machine